HAD BAGI PEZINA MUHSHAN (KAJIAN PERBANDINGAN DALIL) - Khairuddin Khairuddin (Sharia and Law Faculty, 2017)
This study aims to look at the comparative perspective of hudud to sexual intercourse after married. This is based on Qur’anic and Hadith that makes a clear punishment for muhsan and ghairu muhsan. However, in this study has found that there are difference opinion of ulama toward the limit of hudud which referred to contradictive Hadith. In this study, the author conducts the critical sanad as a problem solver to the issue.